2010
DOI: 10.1007/s00426-010-0296-1
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of intuitive versus analytic thinking strategies affects the role of working memory in a gambling task

Abstract: Previous studies found mixed results concerning the role of working memory (WM) in the gambling task (GT). Here, we aimed at reconciling inconsistencies by showing that the standard version of the task can be solved using intuitive strategies operating automatically, while more complex versions require analytic strategies drawing on executive functions. In Study 1, where good performance on the GT could be achieved using intuitive strategies, participants performed well both with and without a concurrent WM lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
2
1
Order By: Relevance
“…It was consistent with previous studies that WM played a role in IGT performance ( Hinson et al, 2002 ; Jameson et al, 2004 ; Pecchinenda et al, 2006 ; Bagneux et al, 2013 ). Nevertheless, these results were not consistent with some studies ( Turnbull et al, 2005 ; Gozzi et al, 2011 ). This might be because we used different versions of IGT, and different secondary task were used.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…It was consistent with previous studies that WM played a role in IGT performance ( Hinson et al, 2002 ; Jameson et al, 2004 ; Pecchinenda et al, 2006 ; Bagneux et al, 2013 ). Nevertheless, these results were not consistent with some studies ( Turnbull et al, 2005 ; Gozzi et al, 2011 ). This might be because we used different versions of IGT, and different secondary task were used.…”
Section: Discussioncontrasting
confidence: 92%
“…Further adaptations were made on the task: first, it was argued that the reward and punishment schedule in the original IGT was too simple ( Gozzi et al, 2011 ). Participants only needed to attend to the value of loss in the task, since the magnitude of wins were fixed (50 or 100) in the task ( Cauffman et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…A second line of research tried to apply a load to WM, with the idea that if the IGT requires WM, then taxing WM should lead to less advantageous decision making on the IGT. Two such studies failed to observe an effect of WM load on decision making under normal IGT conditions [ 12 , 13 ], whereas two other studies observed an effect of WM load [ 14 , 15 ]. Moreover, it has been observed that participants realizing an interfering secondary task - supposed to tax WM - during the first 100 trials of the IGT show a lower number of advantageous decisions in the IGT [ 16 ] – while the same interfering task has no effect on decision making after the 100 th trial.…”
Section: Introductionmentioning
confidence: 99%